Н10 WAVE DIFFRACTION IN A RECTANGULAR WAVEGUIDE BY NARROW WALLS IMPEDANCE BUMP - Logacheva, L. M.; Kutsak, S. V.; Bondarev, V. P. (Radio Electronics, Computer Science, Control, 2010)
Rigorous solution of the principal H10 wave diffraction problem at the joint of regular and non-regular (narrow walls are formed by secondary waveguides) rectangular waveguides has been obtained using the method of projection matching. On the basis of numerical results the dependence of the system diffraction characteristics on its parameters is determined and analyzed.